Innovation, R&D Investment and Productivity in Chile - Roberto Alvarez; Claudio Bravo-Ortega; Lucas Navarro (Inter-American Development Bank (IDB), 2010)
This paper uses two sources of information and different methodologies to analyze the causal effect of product and process innovation on productivity in the Chilean manufacturing industry during the past decade. In general, the evidence suggests there is not a contemporaneous effect of product innovation on productivity, but there is a positive effect of process innovation. This notsignificant effect of product innovation contrasts with evidence of studies for other countries. However, the results show the presence of lagged effects product innovation on productivity two years after innovation. Compared with the case of developed countries, this evidence might be consistent with a very slow process of learning by doing on the part of Chilean firms with regard to mastering new technologies. These slow and frequently uncertain gains in productivity could help to explain the low levels of investment in research and development (R&D) activities by Chilean firms.
Keywords: D22; D24; D92; 330; Productivity; Innovation; Investment; Research and development; Chile